Association between platelet to lymphocyte ratio and plateletcrit with the presence of hyperemesis gravidarum: A case-control study - Massious, Naela Faraj; Jawad, Aryiana Khalis (Zanco Journal of Medical Sciences (ZJMS), 2020)
Background and objective: Hyperemesis gravidarum can be defined as intractable nausea and vomiting, leading to electrolyte imbalance, ketonuria, nutrition deficiency, and weight loss during pregnancy. This study aimed to investigate the association of the platelet to lymphocyte ratio and plateletcrit with the presence of hyperemesis gravidarum. Methods: A case-control study was conducted at Maternity Teaching Hospital in Erbil city, Kurdistan region of Iraq, between January 1st, 2017 and January 1st, 2018. A convenience sample of 120 pregnant women, of which 60 of them with a diagnosis of hyperemesis gravidarum admitted to the emergency department, were regarded as cases. The other 60 visited the outpatient department with mild discomfort, but not having hyperemesis gravidarum were regarded as controls. Age, gestational age, gravida, parity, height, and weight and laboratory parameters, including complete blood count from which we had platelet to lymphocyte ratio and plateletcrit %, were recorded on a specially designed questionnaire. Chi-square test, Fisher’s exact test, Student's t-test, Youden’s index were used to determine the associations. Results: The platelet to lymphocyte ratio and plateletcrit were higher in the hyperemesis gravidarum groups than controls (P <0.001). The area under the curve for platelet to lymphocyte ratio and plateletcrit were 0.887 and 0.936, respectively, with P <0.001. Platelet to lymphocyte ratio >145.07 and plateletcrit >0.205% were significantly related to an increased risk of hyperemesis gravidarum. Conclusion: The platelet to lymphocyte ratio and plateletcrit are higher in hyperemesis gravidarum cases and may have a predictive value of the development of hyperemesis gravidarum as further studies needed in the future to confirm.